Clinical and epidemiological characteristics of a hepatitis E outbreak in an internally displaced persons camp in Kassala, Sudan - Bakhit, Barakat M.; Awad, Kamal M.; Osman, Asim A.; Osman, Makawi A. A. (International Journal of Advances in Medicine, 2026)
Background: Hepatitis E virus (HEV) is a leading cause of acute viral hepatitis in humanitarian settings. In March 2025, a large HEV outbreak occurred in an internally displaced persons (IDP) camp in Kassala, Sudan. The aim of the study was to evaluate the epidemiological and clinical characteristics of the outbreak to inform public health response. Methods: We conducted a descriptive cross-sectional study using secondary data from the Kassala State Ministry of Health for all reported HEV cases between March and June 2025. Data were analyzed for demographic, clinical, and temporal characteristics. Results: A total of 1,041 HEV cases were reported. The mean age was 20.3 years, with the highest attack rates in children and young adults (0-19 years). Females were disproportionately affected (60.7% of cases). The most common clinical presentations were dark urine (83.8%), fever (80.1%), and jaundice (74.4%). The epidemic curve peaked in late March, suggesting a common-source exposure. Only 1.6% of cases were laboratory-confirmed, revealing a significant diagnostic gap. Conclusions: The 2025 Kassala HEV outbreak highlights the vulnerability of IDP populations to waterborne diseases. The findings underscore the urgent need for specific, actionable interventions, including the deployment of rapid diagnostic tests, implementation of point-of-use water treatment, and targeted health education for women and children to prevent future outbreaks.